External validity of post-stroke interventional gait rehabilitation studies. Issue 1 (2nd January 2017) - Kafri, Michal; Dickstein, Ruth
Abstract : Gait rehabilitation is a major component of stroke rehabilitation, and is supported by extensive research. The objective of this review was to examine the external validity of intervention studies aimed at improving gait in individuals post-stroke. To that end, two aspects of these studies were assessed: subjects' exclusion criteria and the ecological validity of the intervention, as manifested by the intervention's technological complexity and delivery setting. Additionally, we examined whether the target population as inferred from the titles/abstracts is broader than the population actually represented by the reported samples. Methods: We systematically researched PubMed for intervention studies to improve gait post-stroke, working backwards from the beginning of 2014. Exclusion criteria, the technological complexity of the intervention (defined as either elaborate or simple), setting, and description of the target population in the titles/abstracts were recorded. Results: Fifty-two studies were reviewed. The samples were exclusive, with recurrent stroke, co-morbidities, cognitive status, walking level, and residency being major reasons for exclusion. In one half of the studies, the intervention was elaborate. Descriptions of participants in the title/abstract in almost one half of the studies included only the diagnosis (stroke or comparable terms) and its stage (acute, subacute, and chronic). Conclusions: The external validity of a substantial number of intervention studies about rehabilitation of gait post-stroke appears to be limited by exclusivity of the samples as well as by deficiencies in ecological validity of the interventions. These limitations are not accurately reflected in the titles or abstracts of the studies.